Do polygenic scores of cerebral small vessel disease MRI markers predict white matter lesions?. (31st December 2021) - de Silva, Eric; Sudre, Carole H; Barnes, Jo; Scelsi, Marzia Antonella; Altmann, Andre
Abstract: Background: Evidence of cerebral small vessel disease (CSVD) is commonly found in those with a diagnosis of Alzheimer's disease (AD) and is associated with T2‐weighted MRI‐visible white matter hyperintensities (WMHs). Here we investigate whether macrostructural and microstructural polygenic risk scores (PRS) predict WMH volumes. Method: We used Genome Wide Association Studies (GWAS), based on UK Biobank (UKB) MRI markers of WMH, Fractional Anisotropy (FA) and Mean Diffusivity (MD) from (Persyn et al., 2020, https://doi.org/10.1038/s41467‐020‐15932‐3) to compute PRS for n=730 participants (following strict quality control) from the AD Neuroimaging Initiative (ADNI) using PRSice. We calculated WMH volumes for ADNI subjects using a Bayesian Model Selection method BaMoS (Sudre et al., https://doi.org/10.1109/TMI.2015.2419072). Linear regression models (with confounds for age, gender, education, APOE4 status, total intracranial volume and five principal components of population structure) were used to test for association (including multiple testing correction) between WMH, FA and MD PRS (based on p‐value thresholds at p=1.0e ‐05 and p=0.5) and WMH volumes in each of three diagnostic groups: Healthy Controls (HC; n=218), Mild Cognitive Impairment (MCI; n=390) and AD (n=122). Result: WMH and FA PRS did not predict WMH volume in the ADNIGO and ADNI2 cohort (Table 1) despite high correlation between BaMoS‐derived and BIANCA‐derived WMH volumes (r=0.84 on 19, 070 UKB subjects). However, MD PRS at the p=0.5 threshold in the MCI group was positively correlated with WMH volume (Table 1) with t=3.4 (FDR‐corrected P=0.0008; Figure 1). Conclusion: Despite a high heritability of WMH (h 2 =0.76; Sachdev et al.. 2016, https://doi.org/10.1161/STROKEAHA.116.012532), unexpectedly, WMH PRS did not predict WMH volume in ADNI in any of the diagnostic groups. The correlation between total WMH estimated with both tools was very high and thus is unlikely the source of this lack of association, however, this may be due to different inclusion criteria for ADNI. The statistically significant relationship in the ADNI MCI group between MD PRS and WMH volume may reflect the early white matter tract damage that is visible before AD manifests and these structural insults become overwhelming. This is reflected in many of the other PRS‐WMH corelations in the MCI group which are borderline statistical significance.